2015
DOI: 10.1111/1365-2745.12436
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance alters beta‐diversity but not the relative importance of community assembly mechanisms

Abstract: Summary1. Ecological disturbances are often hypothesized to alter community assembly processes that influence variation in community composition (b-diversity). Disturbance can cause convergence in community composition (low b-diversity) by increasing niche selection of disturbance-tolerant species. Alternatively, disturbance can cause divergence in community composition (high b-diversity) by increasing habitat filtering across environmental gradients. However, because disturbance may also influence b-diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 38 publications
7
149
3
Order By: Relevance
“…The observed relationships of changes in taxonomic and functional turnover with climatic variance, year‐to‐year predictability, long‐term trends, and extreme events measures at various scales show that more negative changes in turnover, that is, homogenization, occur in unstable environments, while a stable environment maintains spatial turnover and promotes more positive changes. This contrasts with the findings of Martin and Ferrer (2015), who showed that for Mediterranean birds, mammals, amphibians, and reptiles, temporally variable environments maintained higher spatial turnover; however, it supports the suggestion that environmental disturbances contribute to community homogenization through niche selection of disturbance‐tolerant species (Myers, Chase, Crandall & Jiménez, 2015). Environmental stability–spatial turnover relationships appear to be sparse within the literature, and the results found in the present paper open up a potential area of future research to further investigate this relationship.…”
Section: Discussioncontrasting
confidence: 94%
“…The observed relationships of changes in taxonomic and functional turnover with climatic variance, year‐to‐year predictability, long‐term trends, and extreme events measures at various scales show that more negative changes in turnover, that is, homogenization, occur in unstable environments, while a stable environment maintains spatial turnover and promotes more positive changes. This contrasts with the findings of Martin and Ferrer (2015), who showed that for Mediterranean birds, mammals, amphibians, and reptiles, temporally variable environments maintained higher spatial turnover; however, it supports the suggestion that environmental disturbances contribute to community homogenization through niche selection of disturbance‐tolerant species (Myers, Chase, Crandall & Jiménez, 2015). Environmental stability–spatial turnover relationships appear to be sparse within the literature, and the results found in the present paper open up a potential area of future research to further investigate this relationship.…”
Section: Discussioncontrasting
confidence: 94%
“…However, we also found that RC metric was higher than expected at random when S. densiflora was removed, indicating an increased importance of processes that drive community divergence far from the null model expectation (see Myers et al. ). In this context, in a recent work, Guo et al.…”
Section: Discussionsupporting
confidence: 52%
“…In short, the observed b diversity values (b obs ) were compared to b diversity values generated from null models (b null ) and standardized differences between b obs and b null were used as independent estimates of b diversity (b dev ). To determine whether b obs diversity and b dev -diversity differed between the harvest and control treatments, we performed non-parametric analysis of variance based on distance to centroid values (i.e., homogeneity of multivariate dispersion tests) with the betadisper function in R (Anderson et al 2011, Myers et al 2015. First, we created an abundance-based (Bray-Curtis) dissimilarly matrix between all possible paired sites.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…While the removal of biomass was conducted similarly across all experimental sites, repeated harvesting may have altered environmental conditions in ways that allowed for differential rates of mortality, colonization, and varied strength of competition for newly open space, resulting in large differences in community composition among harvested sites (Myers et al 2015). Dissimilarity in ant community composition was largely driven by rare species (e.g., B. depilis, F. incerta, and M. americana) and small-sized nesters (e.g., M. fracticornis and F. vinculans).…”
Section: Harvest Increased B Diversity Of Ants In Grasslandsmentioning
confidence: 99%